1997
DOI: 10.1097/00006123-199709000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Outcome and Radiographic Comparisons between Laminectomy and Laminotomy in the Treatment of Acquired Lumbar Stenosis

Abstract: This study indicates that laminotomy can adequately decompress lumbar canal stenosis, that laminectomy and laminotomy have the same degree of postoperative listhesis, and that the quantitative outcome of any treatment for lumbar stenosis is dependent not only on surgical factors but also on comorbid physical and psychological factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 47 publications
0
49
0
1
Order By: Relevance
“…Direct surgical decompression by laminectomy is a routine option for the treatment of spinal stenosis. A high postoperative incidence of spinal instability and a high associated re-operation rate are reported in laminectomy series [8][9][10][11][12][13][14]. In order to avoid iatrogenic destabilisation, we recommend unilateral laminotomy with bilateral decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Direct surgical decompression by laminectomy is a routine option for the treatment of spinal stenosis. A high postoperative incidence of spinal instability and a high associated re-operation rate are reported in laminectomy series [8][9][10][11][12][13][14]. In order to avoid iatrogenic destabilisation, we recommend unilateral laminotomy with bilateral decompression.…”
Section: Discussionmentioning
confidence: 99%
“…The laminotomy procedure, which decompresses the spine while preserving these midline structures, has been shown to be clinically effective in the treatment of lumbar stenosis. [7][8][9][10][11][12][13][14][15] Studies in calf 16 and porcine 8 models have suggested that laminectomy causes more destabilization of a spinal motion segment than laminotomy and that a lumbar spine with posterior complex integrity is less likely to develop segment instability than a lumbar spine with a compromised anchoring point for supraspinous ligament. To our knowledge, there is no biomechanical human study examining stability of the decompressed spine with the posterior midline ligamentous structures intact.…”
mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) helps to evaluate compression of the roots and cauda equina or spinal cord at upper levels. In cases of stenosis following spinal surgical procedures, con- trast-enhanced MRI is very helpful to differentiate peridural scar formation, recurrent disc herniation, and facet hypertrophy [12,15,18]. Even though some authors conclude that most cases of lumbar spinal stenosis can be managed conservatively, the literature to date has focused primarily on surgical treatment, and studies comparing conservative and surgical management of spinal stenosis are insufficient [1,8,12,14].…”
Section: Discussionmentioning
confidence: 99%